Exploration of Metacognitive Strategies and Multimedia Resources to Improve Students' Listening Comprehension - Febrika Dwi Lestari; Vina Merina Br Sianipar (AL-ISHLAH: Jurnal Pendidikan, 2024)
Strategy and media are important matters in the education field that have a big impact on learning success. This study is designed to explore the effect of metacognitive strategy and multimedia resources on the listening ability of university students. This experimental quantitative study chose 40 second-semester students of the English Department of HKBP Nommensen University Medan as the samples that were divided into experimental and control groups. Then, pretest and post-test were administered to both of the groups to accomplish the aim of the study. The data of this research was taken from the student’s scores on the pre-test and post-test. The result of the test showed that the average score of the experimental group increased from 43.00 in the pre-test to 73.50 in the post-test. While in the control group, the average is 38.50 for the pre-test and 57.25 for the post-test. To complete the research result, the formula of the t-test was applied to the testing hypotheses. It showed that T-calculated T-table, in which T-calculated is 4.160, while the T-table is 2.024. this result indicated that the metacognitive strategy and multimedia resources had a big and significant impact on the students’ listening ability. It means that this strategy and learning media seem to be appropriate models to be used to increase the student’s ability in listening skills.